THE INFLUENCE OF CONSUMER BEHAVIOR AND LIFESTYLE ON SHOE PURCHASING DECISIONS OF LINGGABUANA UNIVERSITY STUDENTS AT PGRI SUKABUMI - Kamil, Muhamad Kaka Milano; Hidayatullah, Ilham; Lisnawati, Euis (JCI Publisher, 2026)
The primary goal of this study was to quantitatively analyze the contribution of consumptive behavior and lifestyle toward shoe purchasing decisions among students at Universitas Linggabuana PGRI Sukabumi. The analysis consistently showed that both independent variables play a significant role in influencing purchasing choices. Specifically, consumptive behavior was found to have a positive and tangible impact on buying decisions when analyzed individually. Similarly, lifestyle also demonstrated a distinct, positive, and significant contribution. When examined simultaneously (Uji F), these two factors were collectively proven to be significant. The model exhibited strong explanatory power, indicating that the majority of the variation in student purchasing decisions can be effectively attributed to their lifestyle trends and high consumption levels. In conclusion, the findings confirm that both lifestyle and consumptive behavior are central and positive drivers in shaping students' shoe purchasing decisions